Differences in cervical length during the second trimester among normal weight, overweight and obese women: A systematic review and meta-analysis - Michail Panagiotopoulos; Vasilios Pergialiotis; Konstantina Trimmi; Antonia Varthaliti; Antonios Koutras; Panagiotis Antsaklis; Georgios Daskalakis (Elsevier, 2024)
Objective: Maternal obesity has been previously linked to increased risk of preterm birth; however, the actual pathophysiology behind this observation remains unknown. Cervical length seems to differentiate among overweight, obese and extremely obese patients, compared to normal weight women. However, to date the actual association between body mass index and cervical length remains unknown. In this systematic review, accumulated evidence is presented to help establish clinical implementations and research perspectives. Methods: We searched Medline, Scopus, the Cochrane Central Register of Controlled Trials CENTRAL, Google Scholar, and Clinicaltrials.gov databases from inception till February 2023. Observational studies that reported on women undergone ultrasound assessment of their cervical length during pregnancy were included, when there was data regarding their body mass index. Statistical meta-analysis was performed with RStudio. The quality of the included studies was assessed using the Newcastle-Ottawa Quality Assessment Scale (NOS). Results: Overall, 20 studies were included in this systematic review and 12 in the meta-analysis. Compared to women with normal weight, underweight women were not associated with increased risk of CL < 15 mm or < 30 mm and their mean CL was comparable (MD −1.51; 95% CI −3.07, 0.05). Overweight women were found to have greater cervical length compared to women with normal weight (MD 1.87; 95% CI 0.52, 3.23) and had a lower risk of CL < 30 mm (OR 0.65; 95% CI 0.47, 0.90). Conclusion: Further research into whether BMI is associated with cervical length in pregnant women is deemed necessary, with large, well-designed, prospective cohort studies with matched control group.